A Comparison of Upper Body Strength between Rock Climbing and Resistance Trained Men - Kristina M. Macias; Lee E. Brown; Jared W. Coburn; David D. Chen (MDPI AG, 2015)
Studies have shown that advanced rock climbers have greater upper body strength than that of novice climbers or non-climbers. The purpose of this study was to compare upper body strength between rock climbing and resistance trained men. Fifteen resistance trained men (age 25.28 ± 2.26 yrs; height 177.45 ± 4.08 cm; mass 85.17 ± 10.23 kg; body fat 10.13 ± 5.40%) and 15 rock climbing men (age 23.25 ± 2.23 yrs; height 175.57 ± 8.03 cm; mass 66.66 ± 9.40 kg; body fat 6.86 ± 3.82%) volunteered to participate. Rock climbing (RC) men had been climbing for at least two years, 2-3 times a week, able to climb at least a boulder rating of V4-5 and had no current injuries. Resistance trained (RT) men had been total body strength training for at least two years, 2-3 times a week with no current injuries. Each participant performed pull-ups to failure, grip strength, and pinch strength. RT were significantly older and heavier than RC. RC performed significantly more pull-ups (19.31 ± 4.31) than RT (15.64 ± 4.82). RC had greater relative pinch strength (R 0.27 ± 0.10 kg/kg; L 0.24 ± 0.07 kg/kg) than RT (R 0.19 ± 0.04 kg/kg; L 0.16 ± 0.05 kg/kg) and greater relative grip strength (R 0.70 ± 0.10 kg/kg; L 0.65 ± 0.12 kg/kg) than RT (R 0.57 ± 0.14 kg/kg; L 0.56 ± 0.15 kg/kg). Overall, RC men demonstrated greater performance in tests involving relative strength when compared to RT men. Rock climbing can promote increased upper body strength even in the absence of traditional resistance training.